2020
DOI: 10.3776/tpre.2020.v10n1p73-91
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Rural School Leaders in a School-Community Partnership

Abstract: Rural schools play central roles in their communities, and rural education scholars advocate for rural school-community partnerships to support school and community renewal. Across the United States, including in rural areas, formal models for school-community partnerships have been scaled up. The literature on rural principals highlights their roles in developing school-community partnerships, yet questions remain as to how school leaders engage in such partnerships. Using boundary-spanning leadership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…The built "support system" helped in developing activities and practices for the diffusion of educational robotics in consideration of local areas' needs, constraints, and possibilities. Thus, their example proofs that for the successful diffusion of technology in education it is important to develop communities and partnerships (Pillay & Hearn, 2009;Rahim & Begum, 2014;Zuckerman, 2020). As Pillay and Hearn (2009) and Rahim and Begum (2014) noted, that when the government, academia, and industry work together, they overcome the issues of rural education and improve its ICT diffusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The built "support system" helped in developing activities and practices for the diffusion of educational robotics in consideration of local areas' needs, constraints, and possibilities. Thus, their example proofs that for the successful diffusion of technology in education it is important to develop communities and partnerships (Pillay & Hearn, 2009;Rahim & Begum, 2014;Zuckerman, 2020). As Pillay and Hearn (2009) and Rahim and Begum (2014) noted, that when the government, academia, and industry work together, they overcome the issues of rural education and improve its ICT diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the findings showed that the diffusion of any educational technology in remote areas would not be possible and sustainable without strong leadership (Ra et al, 2016;Rogers, 2010;Zuckerman, 2020). Ra et al (2016) highlight that weak or absent leadership leads to an absence of educational planning and a misallocation of resources when implementing educational technology.…”
Section: Discussionmentioning
confidence: 99%
“…Places also provide specific resources, opportunities and identities for the actors involved in a CSP. Most importantly, places provide a particular motivation for the formation of a CSP, to answer the needs of a community in a specific location (Zuckerman, 2019), whether it be coral reef protection (Bloomfield & Schleifer, 2017), promoting social inclusion (McDonald, Frost, Kirk-Brown, Rainnie, & Van Dijk, 2010), encouraging sustainable cotton farming (Bitzer & Glasbergen, 2010), reducing race-based discrimination (Ferdinand, Paradies, & Kelaher, 2013) or revitalisation of plantations (van Hille et al, 2019). Hence, places provide CSPs with a formation motivation rationale (Feilhauer & Hahn, 2019), which is to do with the embeddedness of issues in specific locations.…”
Section: Partnerships (2a Andb)mentioning
confidence: 99%
“…Adaptive challengesthose that require a response outside our existing repertoire-often present as a gap between an aspiration and an existing capacity-a gap that cannot be closed by existing modes of operating. (Ancona, 2012, p. 4) Sensemaking is an established framework used by various scholars studying the field of education (Allen & Penuel, 2015;Connery & Weiner, 2021;McHenry-Sorber & Campbell, 2019;Reid, 2020;Watkins, et al, 2020;Zuckerman, 2019). However, a gap exists within the literature as the theory has yet to be used as a framework to study the response of K-12 school leaders to the challenges of COVID-19 in the state of Missouri.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, multiple studies have been conducted to understand how principals made sense of accountability-driven policy initiatives and how it affects their role as school leaders in the future (Reid, 2020;Watkins, et al, 2020). Studies on community building between a school and its community in rural Nebraska and teachers' responses to professional development based on new standards used a sensemaking lens (Allen & Penuel, 2015;Zuckerman, 2019).…”
Section: Extant Literaturementioning
confidence: 99%